2015
DOI: 10.1136/bjophthalmol-2015-306683
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetic retinopathy in individuals with type 2 diabetes who had recorded diabetic retinopathy from retinal photographs in Catalonia (Spain)

Abstract: Background/aimsRetinal photography with a non-mydriatic camera is the method currently employed for diabetic retinography (DR) screening. We designed this study in order to evaluate the prevalence and severity of DR, and associated risk factors, in patients with type 2 diabetes (T2DM) screened in Catalan Primary Health Care.MethodsRetrospective, cross-sectional, population based study performed in Catalonia (Spain) with patients with T2DM, aged between 30 years and 90 years (on 31 December 2012) screened with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
1
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 27 publications
6
32
1
13
Order By: Relevance
“…In our country, the prevalence values of DR were stable throughout the first decade of this century with a small decrease in the incidence of DR. In other parts of Spain, the prevalence of DR remained stable, with lower levels than in other countries, 22 but since 2010 the DR incidence has increased, especially in the DR forms that cause a loss of sight. We therefore decided to analyse our data more accurately and found that any DR increased selectively in some age groups, surprisingly, in the 41–50 and 51–60 age groups ( figure 2 ).…”
Section: Discussionmentioning
confidence: 96%
“…In our country, the prevalence values of DR were stable throughout the first decade of this century with a small decrease in the incidence of DR. In other parts of Spain, the prevalence of DR remained stable, with lower levels than in other countries, 22 but since 2010 the DR incidence has increased, especially in the DR forms that cause a loss of sight. We therefore decided to analyse our data more accurately and found that any DR increased selectively in some age groups, surprisingly, in the 41–50 and 51–60 age groups ( figure 2 ).…”
Section: Discussionmentioning
confidence: 96%
“…There have been many studies on the prevalence of retinopathy. Previous studies, with the number of subjects with T2DM being ∼10 000 or more and published in the past decade, showed the prevalence of any retinopathy to be 30.3% (26 216/86 390) in Wales, 17 16.3% (8584/52 736) in Portugal, 18 12.3% (13 387/108 723) in Catalonia, 19 19.3% (8409/43 523 in newly diagnosed T2DM) in Scotland, 20 and 25.3% (16 094/63 622) in Norfolk. 21 Compared with the studies on retinopathy, there have been fewer studies on the prevalence of neuropathy, and the number of subjects examined was also smaller.…”
Section: Discussionmentioning
confidence: 98%
“…In a crosssectional study of four urban US sites, DR was shown to be correlated with duration of diabetes, but not with smoking status, health insurance status or knowledge of HbA1c level [83]. Risk factors associated with DR in a large screening study in Spain included duration of diabetes, HbA1c levels, blood pressure and hypertension [84]. DR is also associated with the presence of other vascular complications that occur with diabetes, and the presence of such complications should be considered when evaluating a patient's risk of the presence or progression of DR [85].…”
Section: Risk Factorsmentioning
confidence: 99%